PATHOLOGICAL MORPHO-FUNCTIONAL DYSINTEGRATION AS THE KEY PATHOGENETIC MECHANISM OF EXPERIMENATL LIVER CIRRHOSIS - Vastyanov, R.S.; Dzygal, O.F.; Gorlitsyna, О.А.; Mykhailenko, V.L.; Lapshyn, D.Ye.; Nazarenko, O.Ya. (World of Medicine and Biology, 2020)
The purpose of the study is to investigate the liver cirrhosis pathophysiological mechanisms in rats and to investigate the efficacy of pathogenetical correction of these pathology using L–arginine aspartate and tivortin. Experimental studies proved the lipid peroxidation involvement into the liver cirrhosis pathogenetic mechanisms. The data obtained indicate the cellular apparatus of the blood participation in the pathogenetic mechanisms of the hepatocytes lesions. The data received in morphological studies are comparable with the results of biochemical investigations confirming the unified concept of pathological morpho-functional disintegration development in conditions of investigated pathology that is the basis for the multiple organ failure syndrome development. The authors argue that the positive results of both L–arginine aspartate and tivortin using in experimental liver cirrhosis are supposed to be an experimental background of these pharmacons clinical efficacy testing.
Keywords: experimental liver cirrhosis; lipid peroxidation; morphological disturbances; pathophysiological mechanisms; L–arginine aspartate; tivortin; pathological morpho–functional dysintegration